Cost‐effectiveness analysis of silver diamine fluoride to divert dental general anaesthesia compared to standard care. (29th September 2022) - Nguyen, TM; Tonmukayakul, U; Hall, M; Calache, H
Abstract: Background: The aim is to perform a model‐based cost‐effectiveness analysis of a silver diamine fluoride (SDF) protocol intervention to divert dental general anaesthesia (DGA) among Victorian children aged 2–10 years. Methods: Data inputs were based on an Australian single‐cohort 2017/18 study. Intervention costs for standard care were derived from two subgroups of children: (1) children who received standard care without DGA, and (2) children who received standard care with DGA. Two scenarios were modelled due to limited post‐follow‐up data: (1) children receiving SDF had standard care without DGA (base‐case scenario), and (2) children receiving SDF did not receive standard care without DGA (alternative scenario). A simple decision‐tree model with probabilistic sensitivity analysis (PSA) estimated the incremental costs per diverted DGA. Results: The probability of children requiring specialist referral and offered SDF, but the primary carer opted for DGA is 0.124 (SD 0.034), and the probability of children requiring DGA in standard care is 0.346 (SD 0.036). For both the base‐case and alternative scenario, the incremental cost‐effectiveness ratio outcome is dominant and their cost‐effectiveness being either 74.8% or 100% respectively. Conclusions: The SDF protocol intervention is cost‐effective dental caries management option for young children where referral for DGA is considered. © 2022 Australian Dental Association.